2005
DOI: 10.1093/cercor/bhi042
|View full text |Cite
|
Sign up to set email alerts
|

Functional Organization of Ferret Auditory Cortex

Abstract: We characterized the functional organization of different fields within the auditory cortex of anaesthetized ferrets. As previously reported, the primary auditory cortex, A1, and the anterior auditory field, AAF, are located on the middle ectosylvian gyrus. These areas exhibited a similar tonotopic organization, with high frequencies represented at the dorsal tip of the gyrus and low frequencies more ventrally, but differed in that AAF neurons had shorter response latencies than those in A1. On the basis of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

23
263
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 207 publications
(291 citation statements)
references
References 47 publications
23
263
0
Order By: Relevance
“…Tracer injections were, where possible (17/23 injection sites; see Table 1), made in physiologically identified cortical regions. When physiological verification was not possible, the locations of the tracer injections were targeted and assigned to a particular cortical field based on our previous descriptions of ferret auditory cortex (Bizley et al, 2005) and were subsequently confirmed cytoarchitectonically (see below).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Tracer injections were, where possible (17/23 injection sites; see Table 1), made in physiologically identified cortical regions. When physiological verification was not possible, the locations of the tracer injections were targeted and assigned to a particular cortical field based on our previous descriptions of ferret auditory cortex (Bizley et al, 2005) and were subsequently confirmed cytoarchitectonically (see below).…”
Section: Methodsmentioning
confidence: 99%
“…Signals were amplified and digitized for off‐line analysis. Acoustic stimuli were noise bursts and pure tones of varying frequency (150 Hz to 20 kHz) and intensity, as in Bizley et al (2005). …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations